ASSESSMENT OF STUDENT DISCIPLINARY MEASURES ADMINISTERED BY SECONDARY SCHOOL AUTHORITIES IN BUNGOMA EAST SUB-COUNTY, KENYA - Wekesa, Wafula Sammy; Lwangale, David Wafula; Ngome, Prof. Charles K. (IJRDO - Journal of Applied Management Science, 2016)
The study assessed student disciplinary measures administered by secondary schoolauthorities in Bungoma East Sub-County, Kenya. The study adopted descriptive surveydesign and mainly targeted learners who stayed mainly under the care of guardians instead oftheir real parents as well as learners who had parents but such parents that never attended totheir school issues. Simple random sampling was used to select 4 schools from the 35 schoolsin the Sub-County. From the 4 schools, 4 guidance and counseling masters; 4 HOD’s incharge of discipline, and 4 principals were purposively sampled for the study. Thereafter, a10% of learners with indiscipline cases per school were purposefully selected. A similarnumber of learners who enjoyed full parental care at all levels were randomly selected forcomparison purposes. Data was analyzed using descriptive statistics, specifically use ofpercentages and frequencies. The study established that corporal punishment was cherishedby schools. This was attributed to the belief that it is biblically directed that sparing the rodspoils the child. It was also owed to experience where corporal punishment had been seen tocontrol bad behavior. However, this was against the government’s directive on ban ofcorporal punishment. Manual work should be used as form of punishment. Apart from beinga form of punishment, manual work is important in training children to do physical work.Suspension from school was also used as a disciplinary measure. However, expulsion wasrefuted.